Alternatif Pemilihan Laptop Bagi Mahasiswa Di Jakarta Utara Menggunakan Metode Analytic Hierarchy Process - Refael Elnatan; Hendy Tannady (Universitas Putra Indonesia YPTK Padang, 2020)
Laptops are thing that are needed by the community in educational activities and in work activities, but the accuracy in choosing laptops based on needs is difficult because there are many laptop brands with a variety of prices and features. This study discusses the selection of laptops as a daily driver for students in North Jakarta, researchusing the AHP method to analyze several alternatives that have been determined based on filling priority weights between criteria and criteria, and alternatives with alternativesfor each criterion. The results of this study indicate that the price, processor, and RAM criteria are the three biggest criteria determining laptop selection. The alternative chosen in this study is the ASUS A456UR